SISTEM PRODUKSI PADI ORGANIK DI KABUPATEN LAMPUNG TENGAH: ANALISIS USAHATANI DAN PASCAPANEN - Revani Intan Putri; Bustanul Arifin; Sudarma Widjaya (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
This research aims to know the farming income of organic rice; production risk and price risk faced by the organic rice farmers. This research was conducted in North Lampung Regency in March-April 2019. This sample of this research consists of 31 organic rice farmers which are taken by using census method. Thedata analysis method are farming income analysis and risk analysis which uses statistics method by counting variance, standard deviation, and coefficient of variation (CV). The results showed that the average of farming income that was achieved by organic rice farmers amounted to IDR 60,525,621.96. The production and price risk are classified into the low category because the value of CV of production risk is 0.13 and CV of price risk is 0.10.Key words: income, organic rice, risk.